Moving Towards Cashless Society: Malaysian Consumers Intention To Adopt Near Field Communication (Nfc) - Enabled Mobile Payment - Balachandran, Dhaarshini (2022)
The continuous advancement in technology, specifically mobile technologies, has brought many changes to human life, especially after the rise of the deadly Covid-19 virus. Contactless systems have become something that everyone today looks for in everything they take part in. The shift to a cashless society by leveraging mobile payment has become an important agenda for many countries across the globe, even before the pandemic. It is also an important agenda for Malaysia; nevertheless, the technology’s progress rate is relatively slow. The majority of Malaysians are still cash-dependent, while those who opt for mobile payment tend to choose quick response or QR-based mobile payment over near field communication or NFC-based mobile payment, despite the latter’s superiority in terms of safety, convenience, user friendliness, and more. Hence, this study aimed to address Malaysian consumers’ transition to a cashless society by leveraging NFC-enabled mobile payment. To achieve this, an extended DOI Theory as well as the Institutional-based Trust Theory, Network Externalities Theory, Value-based Adoption Model, Status Quo Bias Theory, and Stimulus-Organism-Response (S-O-R) theory were utilised to develop the model of the study.